Application of traction force observer and sliding mode controller for speed in enhancing the stability of electric vehicles - Thi Hoai Thu Anh, An; Van Hoa, Nguyen (Institute of Advanced Engineering and Science, 2025)
With the rapid advancement of electric vehicle (EV) technology, optimizing control and stability has become a key research focus. One major challenge is efficiently distributing traction force while minimizing disturbances under real-world conditions. This paper proposes a traction force observation method combined with a sliding mode speed controller to enhance EV performance. The observation method estimates the traction force from the motor to the wheels and detects disturbances affecting force transmission. This enables optimal traction force distribution among the wheels, reducing slip, improving road grip, and enhancing stability in complex driving conditions. Meanwhile, the sliding mode controller flexibly adjusts traction force as the vehicle navigates various terrains, ensuring stability and safety in hazardous situations. Simulations conducted using MATLAB Simulink and CarSim demonstrate that the proposed system significantly improves EV stability and control performance. Although these results are promising, further studies are necessary to address real-world implementation challenges and optimize the method for practical applications, including parameter tuning, sensor integration, and experimental validation. Overall, this research provides a practical framework for enhancing traction control and vehicle dynamics in future intelligent electric mobility systems.